2018
DOI: 10.7759/cureus.c12
|View full text |Cite
|
Sign up to set email alerts
|

Correction

Abstract: Variability in systemic lupus erythematosus (SLE) disease manifestations is well recognized. Lupus disease activity can range from mild to severe. Fever is a common manifestation of SLE and occurs in 36%-86% of patients. In the Modified Systemic Lupus Erythematosus Disease Activity Index (M-SLEDAI), fever is taken into account as disease activity scoring. Assessment of lupus patients with fever is an important diagnostic challenge, since the initial clinical presentation of a patient with lupus is very similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…14 Cytokines, such as interferon-α and interleukin-1, which are also thermogenic factors, play an essential role in the pathogenesis of lupus. 23 Fever was present in more patients with early onset compared with late-onset disease in a large Canadian study. 24 In our study, fever was reported by a proportion (39%) of participants, by 52.4% in a Euro-Lupus cohort 25 and by 34.5% in early SLE.…”
Section: Discussionmentioning
confidence: 92%
“…14 Cytokines, such as interferon-α and interleukin-1, which are also thermogenic factors, play an essential role in the pathogenesis of lupus. 23 Fever was present in more patients with early onset compared with late-onset disease in a large Canadian study. 24 In our study, fever was reported by a proportion (39%) of participants, by 52.4% in a Euro-Lupus cohort 25 and by 34.5% in early SLE.…”
Section: Discussionmentioning
confidence: 92%